Notes on Early Land Plants Today. 50. Radula sainsburiana is a synonym of R. helix (Radulaceae, Marchantiophyta) - Söderström, Lars; Renner, Matt; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2014)
Radula helix was described as Jungermannia helix from a specimen collected by J.D. Hooker on Hermite Island, Tierra del Fuego during the Antarctic expedition of HM Ships Erebus and Terror.